2004
DOI: 10.1080/10284150400001961
|View full text |Cite
|
Sign up to set email alerts
|

NADPH-diaphorase Histochemical Labeling Patterns in the Hippocampal Neuropil and Visual Cortical Neurons in Weaned Rats Reared during Lactation on Different Litter Sizes

Abstract: Tissue distribution of nitric oxide-synthases was investigated in the rat hippocampus and visual cortex under nutritional changes induced by modification of the litter size. Young (30-45-days-old) rats, suckled in litters formed by 3,6 or 12 pups (called small, medium and large litters, respectively), were studied by using nicotine-adenine-dinucleotide phosphate-diaphorase histochemistry (shortly, diaphorase), a simple and robust procedure to characterize tissue distribution of nitric oxide-synthases. We asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…According to these authors, there was a clear trend, in the malnourished group, to lower values of soma area, dendrite field and branches per neuron. Following the above described evidence, it is reasonable to postulate that part of the changes in cortical excitability demonstrated by CSD in malnourished and overnourished rats could be due to such developmental modifications in brain structure that are dependent on nutrition state, as already stressed by others (Morgane et al, 1978;Rocha-de-Melo et al, 2004;Frazão et al, 2008). In this scenario, the lactation condition was a useful variable to induce changes in baseline excitability (similar to what occurs in neuropsychiatric disorders) and therefore also to study the effects of CES on CSD in animals with different cortical activity as induced by baseline nutritional status.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…According to these authors, there was a clear trend, in the malnourished group, to lower values of soma area, dendrite field and branches per neuron. Following the above described evidence, it is reasonable to postulate that part of the changes in cortical excitability demonstrated by CSD in malnourished and overnourished rats could be due to such developmental modifications in brain structure that are dependent on nutrition state, as already stressed by others (Morgane et al, 1978;Rocha-de-Melo et al, 2004;Frazão et al, 2008). In this scenario, the lactation condition was a useful variable to induce changes in baseline excitability (similar to what occurs in neuropsychiatric disorders) and therefore also to study the effects of CES on CSD in animals with different cortical activity as induced by baseline nutritional status.…”
Section: Discussionmentioning
confidence: 97%
“…By the same logic, one can expect the opposite reaction for the overnourished animals. Rocha-de-Melo et al (2004) assessed morphometric features of nitric oxide activity in rats. In the malnourished group, the labeled-cell density in white matter of area 17 was higher compared to the overnourished rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the suckling condition of the pups can influence developmental processes like neurogenesis, neuronal migration and myelination largely occurring during the lactation period (Morgane et al 1993). Under altered suckling conditions, one or more of these processes could be affected, contributing to change the tissue structural organization and functioning (Morgane et al 1978(Morgane et al , 1993Picanço-Diniz et al 1998;Borba et al 2000;Rocha-de-Melo et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Decreasing or increasing the number of pups to be suckled by one dam can lead respectively to overnutrition or malnutrition (Morgane et al 1978;Plagemann et al 1998;Rocha-de-Melo et al 2004). Since nutrition is a factor that can modulate the brain excitability (Stern et al 1974), we here decided to use this technique in order to study the effects of different lactation conditions on SD.…”
Section: Introductionmentioning
confidence: 99%